Lifestyle and Factors Associated with the Elderly People Referred to the Pension Fund - Neda Barzegar; Maryam Niknami; Leila Mirhadian; Ehsan Kazem Nejad Leili; Sedigheh Pakseresht; M M.Meghachandra Singh (Journal of Holistic Nursing and Midwifery)
Abstract